Legal Education Vision of Visionaries - Tripathi, Bibha (JOURNAL OF INDIAN EDUCATION, 2019)
The Indian society of twenty-first century is tremendously changing in many respects affecting the life and well being of every human being. But there is dearth of positive transformation in every change. The Indian education system in general and the legal education in particular are lacking that charm and glory, whose foundation stone had been laid by the great visionaries of Indian education. Law has been treated as an instrument of social engineering and lawyers as social engineers (Pound,1911), but now it seems that law and legal profession has lost its vision, mission and passion (Pillai, 2008). Therefore, the paper attempts to focus on vision of Indian visionaries on higher education in general and legal education in particular—nourished and cherished by some of India’s most brilliant minds. Its culture, its spiritual and philosophical approach shall undoubtedly inoculate and inculcate those aspirations which are there for the welfare of whole world with an emphasis to reflect upon the ethical dimension so that the quality of education per se can be improved and legal education may play a vital role in social transformation.